2013
DOI: 10.1016/j.molmet.2013.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and epigenetic control of metabolic health

Abstract: Obesity is characterized as an excess accumulation of body fat resulting from a positive energy balance. It is the major risk factor for type 2 diabetes (T2D). The evidence for familial aggregation of obesity and its associated metabolic diseases is substantial. To date, about 150 genetic loci identified in genome-wide association studies (GWAS) are linked with obesity and T2D, each accounting for only a small proportion of the predicted heritability. However, the percentage of overall trait variance explained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
79
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(83 citation statements)
references
References 130 publications
1
79
0
3
Order By: Relevance
“…Accordingly, genomewide association studies (GWAS) of common single nucleotide polymorphisms in large cohorts have established associations between ;100 genes and T2D (1)(2)(3)(4). However, these associations explain only a small portion of the total heritability.…”
mentioning
confidence: 99%
“…Accordingly, genomewide association studies (GWAS) of common single nucleotide polymorphisms in large cohorts have established associations between ;100 genes and T2D (1)(2)(3)(4). However, these associations explain only a small portion of the total heritability.…”
mentioning
confidence: 99%
“…Hence, both, glucose and palmitate are able to affect the binding of transcription factors that control the activity of the insulin promoter, pointing to an involvement of these regulators of gene expression in the mechanisms of glucolipotoxicity (68) . Emerging evidence suggests an impact of dietdependent epigenetic modifications in the aetiology of metabolic disorders (69) . Hu et al (70) observed an aberrant DNA methylation profile in β-cells cultured for 1 month in a medium containing high glucose and lipid concentrations.…”
Section: Impact Of Nutrients On β-Cell Gene Expressionmentioning
confidence: 99%
“…People with a family history of T2DM have more six and three times higher risk of developing this disease than unrelated individuals, respectively 18,19 . More than 70% of T2D risk has been attributed to genetics, with multiple genes involved and different combinations of genes playing roles in different subsets of individuals are involved in T2DM 20 . Those that have garnered the most attention are the ATP-binding cassette transporter subfamily C member 8 (ABCC8) gene; the KCNJ11 gene and the peroxisome proliferator-activated receptor-gamma (PPARG) gene.…”
Section: Role Of Genetics In the Development Of Type 2 Diabetes Mellitusmentioning
confidence: 99%